Coping Mechanism Towards Academic Stress Among Students: An Analysis From Islamic Perspective - Mohd Zaliridzal Bin Zakaria; Nurul Izzati Mohd Rezal; Abdul Rashid Bin Abdul Aziz; Nurhafizah Binti Mohd. Sukor; Muhammed Fauzi Othman; Mohd Azhar Abd. Hamid (USIM Press, 2024)
Academic stress can have a negative effect on a student's cognitive, emotional and behavioural well-being. Furthermore, academic stress could also cause a decline in student’s academic performance. Therefore, it is necessary for the student to be able to cope and relieve stress. Religious coping strategies are one of the effective ways in overcoming academic stress. This study was aimed to explore and understand students' experiences of religious coping methods when facing academic stress. A qualitative method by using interview was used. A total of five respondents from public university were involved. The data from interview were analysed by using thematic analysis from five respondents. This study discovered three specific religious coping behaviour that were employed to cope with academic stress; 1) worship in the heart, 2) worship verbally and, 3) worship by action. It has also identified three themes on the impact of religious coping on 1) cognitive, 2) emotional and 3) behaviour. From this study, it can be concluded that specific religious coping behavior which had been used by the students is helpful for them in coping with academic stress. The knowledge and awareness of the internal and external stressors also can help the students to identify the best solution and coping mechanism to manage the stress. These coping behaviors also help the students to have a better understanding on how religious coping can affect students in term of cognitive, emotion and behavior.